2018
DOI: 10.1155/2018/2358690
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Associations of Peripheral Retinopathy: Baseline Study of Guangzhou Office Computer Workers

Abstract: Purpose To determine the prevalence of peripheral retinopathy and its associated risk factors among a sample of Guangzhou office computer workers. Methods A cross-sectional study of Guangzhou Chinese computer workstations and operators in different departments and units of the Guangzhou Power Supply Bureau, China, in 2016. Peripheral retinopathy was recorded and analyzed using a scanning laser ophthalmoscope (SLO; Optos, Daytona, United Kingdom) and slit-lamp microscopy combined with a three-mirror contact len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In general, the retinal changes in high myopia are believed as resulting from the mechanical elongation of the scleral caused by the excessive axial elongation of the eyeball. In several studies, it has been demonstrated that the increased prevalence of PRC was associated with the rise of either axial length (AL) or spherical equivalent refraction (SER) [5,12,13,9,14]. Therefore, it is speculated in this study that the thinning of the posterior scleral causes the increase of axial length and elongation of the retinal, thus leading to peripheral retinal changes.…”
Section: Introductionmentioning
confidence: 76%
“…In general, the retinal changes in high myopia are believed as resulting from the mechanical elongation of the scleral caused by the excessive axial elongation of the eyeball. In several studies, it has been demonstrated that the increased prevalence of PRC was associated with the rise of either axial length (AL) or spherical equivalent refraction (SER) [5,12,13,9,14]. Therefore, it is speculated in this study that the thinning of the posterior scleral causes the increase of axial length and elongation of the retinal, thus leading to peripheral retinal changes.…”
Section: Introductionmentioning
confidence: 76%
“…From 350 BC to now, literature has showed hypotheses about etiology of myopia such as lack of enough outdoor activities and too long time of near work 1 , literature suggested that blue light from screen may correlate with myopia 3,4 , but the identical effect of blue light remains unclear [3][4][5] . The specific causes of myopia remain undefined 1,6,7 .…”
Section: Textmentioning
confidence: 99%
“…From 350 BC to now, literature has showed hypotheses about etiology of myopia such as lack of enough outdoor activities and too long time of near work 1 , literature suggested that blue light from screen may correlate with myopia 3,4 , but the identical effect of blue light remains unclear [3][4][5] . The specific causes of myopia remain undefined 1,6,7 .…”
Section: Textmentioning
confidence: 99%